Effect of Corporate Social Responsibility and Corporate Governance on Corporate Resilience During Pandemics - Bahari, Asniati; Sang, Lim Thien; Yuskar, Yuskar; Astari, Silvy; Annisa, Safira (Management Institute Faculty of Economics Universitas Andalas, 2025)
The purpose of this study is to compare the effects of Corporate Social Responsibility (CSR) and Corporate Governance (CG) on Corporate Resilience (CR) during the first and second waves of COVID-19 in Indonesia and Malaysia. Data for this study were collected from companies listed on the IDX80 of the Indonesia Stock Exchange and the FTSE Bursa Malaysia 100 of the Bursa Malaysia. STATA 14.2 was used for data analysis. The results indicate that in Indonesia, Environmental Disclosure, Social Disclosure, Board of Directors Size, and Audit Committee Size have a significant effect on CR, but not Economic Disclosure and Board of Commissioners Size. In Malaysia, only the size of the Audit Committee has a significant effect on the CR. On the other hand, during the second wave of the pandemic in 2021, CSR and CG did not significantly impact CR for Indonesia and Malaysia. This study shows that internal factors such as CSR and GC do not affect investors' decisions to buy stocks during pandemics. Future research should consider including additional variables, not limited to internal factors, but external factors such as inflation rate and interest rate. Future researchers may need to further combine financial and non-financial data to examine if these factors influence investor decisions to buy stocks during pandemics.